Metodologi Tafsir Lokal Nusantara: Analisis Komparatif atas Tafsir Rahmat karya Oemar Bakry dan Rangkaian Cerita dalam Al-Qur’an karya Bey Arifin - Al Adawiyah, Abidah; Elly, Dinda Masytoh; Musyarrofah (Javano Islamicus, 2025)
Comparative studies on local Qur’anic exegesis in Indonesia remain limited, even though such works reflect the distinctive intellectual dynamics of Nusantara Islam. Tafsir Rahmat by Oemar Bakry and Rangkaian Cerita dalam Al-Qur’an by Bey Arifin are two local interpretations written by scholars from similar backgrounds and periods but exhibiting significant methodological differences. Both were composed to address the needs of Indonesian readers for accessible and socially relevant understandings of the Qur’an. This study aims to analyze and compare their interpretative methodologies using a qualitative method and comparative analysis through library research. The findings show that Oemar Bakry emphasizes systematic structure and linguistic clarity to prevent misinterpretation of the Qur’anic text, whereas Bey Arifin employs a narrative approach that explores ethical and spiritual wisdom from Qur’anic stories. This research enriches Indonesian Qur’anic studies through two distinct yet complementary models of local exegesis: textual-rational and contextual-narrative.